The therapeutic effect of viscous solution of curcumine in the treatment of recurrent aphthous stomatitis (RAS) - Maha T Al-Saffar (University of Mosul, College of Dentistry, 2006)
Abstract Aim: To determine the various therapeutic effect of different concentrations of viscous curcumine solution on the healing of ulcer in patients with recurrent aphthous stomatitis (RAS). Materials and Methods: A total of 83 patients with RAS divided into four groups: Group A: Thirty patients received viscous solution of curcumine 10%; Group B: Thirty three patients received viscous solution of curcumine 50%; Group C: Ten patients without treatment (control negative); and Group D: Ten patients received glycerin treatment (control positive). Results: Females were more affected than males with RAS (69.9% female and 30.1% male) and upper and lower labial mucosa were the most common site of the lesion. The results also showed significant difference between complete healings in patients using viscous solution of curcumine 50% and 10% respectively, and patients without treatment (control negative), while there was no significant difference between the complete healing in patients use 50% of solution and 10 % of the same solution. Conclusion: Topical application of viscous solution of curcumine at 10% and 50% showed a good percentage of complete healing of ulcer in patients with RAS and further study for its effect on other oral lesion may be recommended.